Retracted: Image Analysis System of Intelligent Smart Home Based on VR - Chengmin Zhou; Ting Huang; Liang Shuang (IEEE Access)
With the increasing aging today, the rich life experience has become a topic that people are urgently concerned about. This research mainly discusses the research and application of VR-based smart home image analysis system. This research combines the intelligent design and implementation of the image analysis system of VR technology. The system uses 2D image processing, segmentation, and recognition to filter out information that is of interest to the image, which is helpful for a reasonable plan for smart homes. During the experiment, a mixed model was used to model the background scene, the background difference method was used to detect the moving target in the image, and then the face detection of the moving target was performed. Through such simple real-time image processing, the necessity of real-time video monitoring is realized. After that, the abnormal image data can be saved to provide effective evidence, and the system will issue a warning after detecting the abnormality, which can effectively monitor specific areas such as home. 110 frames of video clips of people actually walking indoors are used for face detection. Experimentally, the acquisition speed of the VR technology camera is 24 frames per second, and the resolution is 420*250. The research results show that image processing is an indispensable part of the intelligent process of video surveillance. It can also be said that the image processing technology of VR technology is more suitable for the smart and suitable home.